A2 2 Damped Bungee Jumping - Cooper, Samuel; Steele, Ethan; Hamade, Ceres (Physics Special Topics, 2023)
In this paper we were able to critically damp a bungee jump system by finding the required damping coefficient c and spring constant k. We found these to be c = 79.27 Ns/m and k = 19.5 N/m. By comparing to a standard value we found that our result was reliable and of a similar magnitude.